Concurrent Diffuse Dural and Leptomeningeal Enhancements in Brain Magnetic Resonance Imaging Following a Mild COVID-19 Infection: A Novel Case Report and Review of Literature - Bawand, Rashed; Ghiasian, Masoud; Samadyan, Mustapha (Current Medical Imaging, 2024)
Introduction During the COVID-19 pandemic, various complications have been reported in patients with this infection worldwide, including a wide range of neurological disorders. In this study, we have reported a novel neurological complication in a 46-years-old woman who was referred due to a headache following a mild COVID-19 infection. Also, we have had a quick review of previous reports of dural and leptomeningeal involvements in COVID-19 patients. Case Report The patient's headache was persistent, global, and compressive with radiation to the eyes. The severity of the headache was increased during the disease course and was exacerbated by walking, coughing, and sneezing but decreased with rest. The high severity of the headache disrupted the patient’s sleep. Neurological examinations were completely normal, and laboratory tests did not have abnormal findings except for an inflammatory pattern. Finally, in the brain MRI, a concurrent diffuse dural enhancement and leptomeningeal involvement were observed, which is a new finding in COVID-19 patients and has not been reported so far. The patient was hospitalized and treated with Methylprednisolone pulses. After completing the therapeutic course, she was discharged from the hospital in good condition and with an improved headache. A repeated brain MRI was requested 2 months after discharge, which was completely normal and showed no evidence of dural and leptomeningeal involvements. Conclusion Inflammatory complications of the central nervous system caused by COVID-19 can occur in different forms and types, and clinicians should consider them.
Keywords: Neuroimaging